Candidate genes for domestication and resistance to cold climate according to whole genome sequencing data of Russian cattle and sheep breeds - N. S. Yudin; D. M. Larkin (Вавиловский журнал генетики и селекции)
It is known that different species of animals, when living in the same environmental conditions, can form similar phenotypes. The study of the convergent evolution of several species under the influence of the same environmental factor makes it possible to identify common mechanisms of genetic adaptation. Local cattle and sheep breeds have been formed over thousands of years under the influence of domestication, as well as selection aimed at adaptation to the local environment and meeting human needs. Previously, we identified a number of candidate genes in genome regions potentially selected during domestication and adaptation to the climatic conditions of Russia, in local breeds of cattle and sheep using whole genome genotyping data. However, these data are of low resolution and do not reveal most nucleotide substitutions. The aim of the work was to create, using the whole genome sequencing data, a list of genes associated with domestication, selection and adaptation in Russian cattle and sheep breeds, as well as to identify candidate genes and metabolic pathways for selection for cold adaptation. We used our original data on the search for signatures of selection in the genomes of Russian cattle (Yakut, Kholmogory, Buryat, Wagyu) and sheep (Baikal, Tuva) breeds. We used the HapFLK, DCMS, FST and PBS methods to identify DNA regions with signatures of selection. The number of candidate genes in potentially selective regions was 946 in cattle and 151 in sheep. We showed that the studied Russian cattle and sheep breeds have at least 10 genes in common, apparently involved in the processes of adaptation/selection, including adaptation to a cold climate, including the ASTN2, PM20D1, TMEM176A, and GLIS1 genes. Based on the intersection with the list of selected genes in at least two Arctic/Antarctic mammal species, 20 and 8 genes, have been identified in cattle and sheep, respectively, that are potentially involved in cold adaptation. Among them, the most promising for further research are the ASPH, NCKAP5L, SERPINF1, and SND1 genes. Gene ontology analysis indicated the existence of possible common biochemical path-ways for adaptation to cold in domestic and wild mammals associated with cytoskeleton disassembly and apoptosis.